Answer:
3
Step-by-step explanation:
I say it is 3 because 2 * 3 = 6
6/2=3
I hope this helps you:)
(-1-3i)(-6-i)
=6+i+18i+3i^2
=3i^2+19i+6. Hope it help!
Answer:
f(x)=x(x-5)(x+2)
Step-by-step explanation:
Since the steps of the factorization of the polynomial f(x) is not given, I will proceed to give the correct factorization of f(x).
f(x)=x³-3x²-10x
First, we factor out x since it is a common term.
f(x)=x(x²-3x-10)
Next, we factorize the quadratic expression x²-3x-10.
f(x)=x(x²-5x+2x-10)
f(x)=x(x(x-5)+2(x-5))
f(x)=x(x-5)(x+2)
The correct factorization of the polynomial f(x)=x³-3x²-10x is: f(x)=x(x-5)(x+2)
Answer:
What are you asking?
Step-by-step explanation: